Gender Based Violence in North Macedonia: Cultural, Legal, and Economic Perspectives Under the Istanbul Convention - Ejupi Fjolla; Arifi Besa (SEEU Review)
Gender-based violence (GBV) is one of the most widespread phenomena globally. As one of the most severe forms of violence, it seriously violates fundamental human rights and freedoms, manifesting itself on both national and international levels. North Macedonia, like many other countries, is significantly affected by this issue. As a signatory to the Istanbul Convention, North Macedonia has undertaken a series of measures aimed at preventing and protecting individuals from GBV. However, due to persistent shortcomings and influencing factors particularly cultural, legal, and economic efforts to combat this phenomenon remain insufficient and call for a more serious and inclusive approach.